Prescription patterns of inhaler medications from 2017 to 2023: A retrospective study using Ontario administrative healthcare data - Anthony Train; Krishna K. Vemuri; Angela Coderre-Ball; Javier Silva-Valencia; Declan Mulligan; Debra A. Butt; Jessica Gronsbell; Braden O’Neill; Andrea Gershon; Karen Tu (PLoS ONE, 2026)
Background Inhalers are essential for respiratory disease management, but commonly used metered-dose inhalers (MDIs) can often be replaced, when clinically appropriate, with lower-emission alternatives such as dry powder inhalers (DPIs) or soft mist inhalers (SMIs). The COVID-19 pandemic may have influenced prescribing patterns. We aim to describe changes in inhaler prescription trends and determine whether MDI use decreased during the pandemic. Methods and findings Retrospective cohort study using Ontario’s health administrative data. Individuals aged 65 and older with new inhaler prescription instances from April 1, 2017, to March 31, 2023, were included. Monthly prescription event rates by inhaler type and socioeconomic factors were modeled for pre-pandemic (April 2017–March 2020) and pandemic (April 2020–March 2023) periods using interrupted time series and Generalized Additive Models to account for autocorrelation and seasonality. 750,517 new inhaler prescriptions were made during the study period. A significant drop was observed at the pandemic’s onset. MDIs were the predominant type of inhaler initially prescribed for both pre-pandemic ~77% and pandemic ~70% periods. The proportion of DPI initial prescriptions modestly increased from ~17% to ~23% and SMI initial prescriptions remained similar. Inhaler prescription rates did not significantly differ across sex, income quintiles, or rurality. Conclusions The COVID-19 pandemic disrupted inhaler prescribing patterns in Ontario, leading to a temporary decline in new prescriptions. Despite environmental and guideline recommendations, MDIs continued to dominate prescribing practices. These findings underscore the need for targeted interventions to align clinical practices with current guidelines and environmental sustainability goals.